How and Where Do We Ask Sensitive Questions: Self-reporting of STI-associated Symptoms Among the Iranian General Population - Maryam Nasirian; Samira Hosseini Hooshyar; Ali Akbar Haghdoost; Mohammad Karamouzian (Kerman University of Medical Sciences, 2018)
Background Reliable population-based data on sexually transmitted infections (STI) are limited in Iran and selfreporting remains the main source of indirect estimation of STI-associated symptoms in the country. However, where and how the questions are asked could influence the rate of self-reporting. In the present study, we aimed to assess what questionnaire delivery method (ie, face-to-face interview [FTFI], self-administered questionnaire [SAQ], or audio self-administered questionnaire [Audio-SAQ]) and setting (ie, street, household or hair salon) leads to more reliable estimates for the prevalence of self-reported STI-associated symptoms. Methods This cross-sectional study was conducted in winter 2014 on a gender-balanced (50.0% men) sample of 288 individuals aged 18-59 years old in Kerman, Iran. Respondents were recruited in (a) crowded public places and streets, (b) their households, and (c) hair salons. Data was collected on history of current and 6-month (ie, past 6 months) STI-associated symptoms. Three different methods including FTFI, SAQ and or Audio-SAQ were applied randomly in households and non randomly in streets and hair salons to collect data among the respondents. Generalized estimating equation (GEE) was used to compare the settings and methods separately. Results A total of 2.8% of men and 9.4% of women self-reported at least one STI-associated symptom. Respondents were significantly more likely to report STI-associated symptoms when completing questionnaires on the street compared to their household (P = .0001). While women were less likely to report symptoms in FTFI compared to SAQ (P = .036), no significant differences were found between men's responses across different methods (P = .064). Conclusion Further research is needed to evaluate the effect of different combinations of methods and settings to find the optimal way to collect data on STI-associated symptoms.